2012
DOI: 10.1089/lap.2012.0142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical and Functional Outcomes of Minimally Invasive and Open Pyeloplasty

Abstract: Minimally invasive pyeloplasty has low morbidity, short length of stay, and less blood loss compared with open surgical repair. It is an effective and feasible minimally invasive treatment modality for ureteropelvic junction obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…[11] In another study, surgical, and functional outcomes of 20 patients who had undergone minimally invasive transperitoneal pyeloplasty (13 robotic, and 7 laparoscopic procedures), and 22 cases who experienced open pyeloplasty were compared. [12] Operative times did not differ significantly between groups, while amount of bleeding, hospital stay, and time to removal of the drain were found to be significantly shorter in the minimally invasive group. Radiological, and symptomatic improvement rates were detected as 95.5, and 95% in the open surgery, and minimally invasive groups, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…[11] In another study, surgical, and functional outcomes of 20 patients who had undergone minimally invasive transperitoneal pyeloplasty (13 robotic, and 7 laparoscopic procedures), and 22 cases who experienced open pyeloplasty were compared. [12] Operative times did not differ significantly between groups, while amount of bleeding, hospital stay, and time to removal of the drain were found to be significantly shorter in the minimally invasive group. Radiological, and symptomatic improvement rates were detected as 95.5, and 95% in the open surgery, and minimally invasive groups, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…9,10 The advantages of robot-assisted surgery over conventional laparoscopy include elimination of surgeon hand tremor, conceivably a shorter learning curve, especially for intracorporeal suturing because of the wristed instruments, and a shorter operative time. 9,11 The shorter operative time for robot-assisted laparoscopic pyeloplasty (RLP) seems to be more and more prominent in recently published studies.…”
mentioning
confidence: 99%
“…Published studies that compare LP versus RLP have mostly reported a shorter operative time with RLP, mainly in the 10-to 30-minute range. [9][10][11][12][13] This difference may be thought to depend mainly on the surgeon's comfort level with laparoscopic suturing, which arguably is the rate-limiting step of the procedure. These studies do not show any significant difference between the two techniques in terms of length of stay in hospital, success rate, complications, and safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, efficacy of laparoscopic approach has been compared with traditional open pyeloplasty, and similar success rates have been reported. [12][13][14][15] Procedural success rate varies between 88-100%, based on subjective, and objective success criteria. [16] Although when compared with open surgery, lesser incisional morbidity, postoperative pain, and shorter hospitalization period, requirement for highly experienced suturing technique, and longer operative times are seen as disadvantages of this method.…”
mentioning
confidence: 99%